The influence of team management competencies on high-quality development of Chinese wellness sport enterprises - Menghan, Wu; Rattanapun, Supot (Edelweiss Applied Science and Technology, 2024)
The high-quality development has become a new idea for the Chinese sports industry. High-quality development has become the main direction and theme of the development of China's sports industry. This research aims to study 1) Team Management Competencies and development level of High-Quality Development of Chinese Sport Enterprises. 2) To study mediating role of Culture communication between Team Management Competencies and High-Quality Development of Chinese Sport Enterprises and 3) To develop in the future team management of Chinese Sport Enterprises. The mixed research method of 532 valid data were obtained through the questionnaire survey, and the empirical test of the theoretical model was completed by using the method of structural equation model. The research shows that Personal quality (0.231), Cognitive ability (0.215), Self-development (0.312), Team management (0.161) and Cultural communication (0.156) has a significant positive impact on the high-quality development of enterprises. The Mediating roles of Cultural communication effected (0.161) on the personal quality, Self-development (0.196), characteristics of enterprise leadership (0.198) with high-quality development of enterprises. Sports enterprise training has a positive role in cognitive ability (0.416) and team management (0.222) on the high-quality development of sports enterprises. In view of the practical difficulties such as imperfect management team and shortage of management talents in China, we put forward the practical path of cultivating team management talents in the field of sports enterprises and accelerating the high-quality development of sports enterprises. Finally, the research results have theoretical and practical significance for the healthy and sustainable development of Chinese wellness sports enterprises.